Pengaruh Green Culture, Green Transformational Leadership , Green Human Resource Management Terhadap Green Organizational Citizenship Behavior - Alfian Nugroho, Muhammad; Tiarapuspa, Tiarapuspa (Rifa'Institute, 2023)
The aim of this research is to analyze the effect of green culture, green transformational leadership, green human resource management on green organizational citizenship behavior among employees of PT. Rita Ritelindo in Cilacap. Data were collected from two hundred and fifty one employees of PT. Rita Ritelindo in Cilacap with the data collection technique used was purposive sampling. The hypothesis test used in this research is Structural Equation Modeling (SEM) analysis. The results of testing the hypothesis in this study indicate that there is a positive effect of green culture, green transformational leadership, green human resource management on green organizational citizenship behavior. The managerial implication in this research is how managers should have more frequent conversations or discussions about environmental issues, because environmental factors cannot be predicted, managers must also be braver to be more responsible for encouraging employees to achieve the company's green goals and leaders as well must consider green innovation movements with employees to create a green environment within the company, and also management must have the courage to acknowledge green initiatives publicly so that employees are aware of the importance of being environmentally friendly, and managers are expected to be more courageous in making new practices to improve environmental performance organization in order to create an environment that is healthy, safe and can provide comfort to every employee.